Political Studies Association Specialist Group of the Year 2025 - Venizelos, Giorgos (My University, 2026)
The Populism Specialist Group (PSA) that I convene received the prize of the Specialist Group of the year 2025 for having raised awareness of politics and contributed to the discipline. We were received the award at the annual PSA conference in Birmingham in April 2025.
Keywords: Sciences